Clinical significance of viridans streptococci isolated from blood cultures. - Swenson, F J (1982)
The clinical significance of viridans streptococci isolated from the blood cultures of 86 patients was determined. Isolates that were significant or suggestive of infection represented only 21% of the cases. Among 54 isolates for which the species was known, Streptococcus sanguis II was the most common. However, a significant association between species and clinical significance was not found.